KEJAKSAAN RI DALAM LEMBAGA NEGARA - Siregar, Yessyurun Oscar Janfaron; Sitabuana, Tundjung Herning (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The Prosecutor's Office of the Republic of Indonesia is a state institution that exercises state power, especially in prosecution, the Prosecutor's Office as the authorized body in law enforcement and justice is led directly by the Attorney General who is appointed by and responsible to the President of the Republic of Indonesia. The Attorney General's Office, the High Prosecutor's Office, and the State Attorney's Office are state powers, especially in the field of prosecution, where all of them are a whole and inseparable whole. The research method that I use is a type of Normative Juridical research method by researching literature materials.